Monitoramento remoto preventivo de pacientes com doenças cardiovasculares utilizando dispositivo móvel como agente inteligente - Silva, Manuella Dias Carvalho (2012)
Several Governments and countries have shown great interest in defining public policies to reduce spending on health services. In this way, several researchers have sought to develop solutions that reduce such costs. Among these solutions are the remote monitoring systems of the State of health of critical patients, those suffering from heart disease, chronic diseases or elderly who need continuous care. These systems allow the identification of risk situations and the adoption of preventive procedures, reducing health spending. In addition, they allow an improvement in quality and lifetime of your users. Several approaches to the construction of these systems. Generally, they are divided into two main groups: the home care and the furniture. The approach used in this paper advocates the use of mobile monitoring systems can be more efficient, since the health monitoring will be carried out regardless of locale or patient drive. The work presented here makes use of pervasive devices for monitoring of the health status of patients with cardiovascular diseases, which are the biggest cause of death in the world. In this sense, this dissertation contributes with an application for use in mobile phones that act as an intelligent agent to the preventive monitoring of cardiovascular diseases, using a rules-based intelligence engine. This application, which has received the name of MonitorPrevIntel, based on the continuous reading of five physiological signals, detect abnormal situations of danger for the health of your server, and emits alarm procedures. To detect anomalous situations the application uses a mechanism fully embedded intelligence on the mobile phone, with custom knowledge base for each user. The alarms emitted by the system warn the user about the detection of abnormal situations and advise, via SMS messages, or trigger, via phone call, a medical center about this situation. The MonitorPrevIntel operation is controlled by your intelligence mechanism, based on the State of health of the user, allowing the same run autonomously, independently of the user activation.